Employability pathways for young adults: lived experiences of learners and practitioners in Youth Guarantee programmes. Issue 1 (2nd January 2020) - Boeren, Ellen; Mackie, Alan; Riddell, Sheila
ABSTRACT: Until today, thousands of young adults still dropout of school with no or low qualifications and experience difficulties in entering the labour market. The European Commission offers funding and opportunities for young adults to enter employability enhancing training, often organised under its flagship initiative 'The Youth Guarantee'. The aim of these programmes is to make young adults a work, training or educational offer within four months of their start into this initiative. In this paper, we critically explore the concept of employability and focus on the roles of both the young adults undergoing training interventions, but also of practitioners whose work is ideally embedded within the local context of the labour market and the economy. We were interested in the participation experiences by both groups to analyse the strengths and weaknesses of these programmes. Evidence from interviews demonstrated that learners and practitioners were generally satisfied with the interventions, although individualised support was preferred over group-based activities. Working with stakeholders was strongly recommended for this target group who tends to experience cumulative disadvantages. Long-term follow-up of participants' destinations will provide better evidence on the effectiveness of these programmes.